Landscapes of welfare: concepts and cultures of British women's philanthropy 1918-1939 - Colpus, E (2011)
This thesis offers a new conceptual framework for the study of women’s philanthropy between the end of the First World War and the beginning of the Second World War. Contesting the dominant historiographical narrative which essentialises the association of women with philanthropy, it argues that interwar female philanthropy operated through an inherently creative and flexible methodology. By interrogating gender as a category of analysis alongside other definitional variables of generation, religion, informal and formal modes of influence, and professionalisation, it reveals female philanthropy as an intellectual, as much as a practical endeavour, through which women philanthropists sought to achieve and encourage self-development and societal improvement. Moving beyond a social history framework that concentrates on philanthropic activity in terms of its relationship to social policy, six thematic chapters argue for the critical significance of concepts of language, performance and space in the meanings and presentations of interwar female philanthropy. A central remit of the thesis is to relate the social and cultural processes that underpinned women’s philanthropy between the wars to the subjective experiences of the individual women who engaged them. The thesis examines the personal archives, published oeuvres and publicity materials (alongside presentations of philanthropy in public discourse) of four philanthropic women who achieved celebrity in the interwar period: Evangeline Booth, Lettice Fisher, Emily Kinnaird and Muriel Paget. It interrogates the contemporary meanings attached to female philanthropy in a period of transformations in mass transport, mass communication and mass democracy, and in women’s position within society. An analysis of this process sheds new light on the historiography of work, civil society and citizenship. Problematising the centrality placed on the national as a sphere of citizenship (embodied in the state), the thesis reveals the critical interconnections between the local and global domains in female philanthropists’ visions. It also illuminates the hitherto underexplored connections between philanthropy, celebrity, the mass media and mass culture. Far from outmoded, female philanthropy lay at the heart of interwar cultural transformations. Female philanthropists contributed dynamically to debates about civil agency and sought to remap the contours of a good society.